Cervical cancer burden and attributable risk factors across different age and regions from 1990 to 2021 and future burden prediction: results from the global burden of disease study 2021 - Cheng, Lu-yao; Zhao, Ji-qi; Zou, Ting-ting; Xu, Zhong-hua; Lv, Yin (Frontiers in Oncology, 2025)
BackgroundCervical cancer (CC) is a global public health problem. We aimed to evaluate the global and regional CC burden between 1990 and 2021, identify the attributable risk factors, and project its burden up to 2035.MethodsData were extracted from the Global Burden of Disease Study 2021, and the CC incidence, mortality, age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), age-standardized disability-adjusted life years (DALYs), and attributable risk factors from 1990 to 2021 were analyzed. The impacts of geographical variations, different age groups, and the socio-demographic index (SDI) on CC morbidity and mortality measurements were assessed. The attributable risk factors to CC death and DALY were evaluated, and the incidence, mortality, and DALYs to 2035 were projected.ResultsGlobally, the number of CC cases has increased from 409,548.49 cases in 1990 to 667,426.40 cases in 2021. However, the ASIR decreased from 18.11 to 15.32 per 100,000, with the greatest ASIR decrease in high SDI regions (estimated annual percentage change: -1.41). Between 1990 and 2021, the global ASDR decreased from 9.68 to 6.62 per 100,000, and the rate of age-standardized DALYs decreased from 330.11 to 226.28 per 100,000. However, these improvements were not consistent across different SDI regions. The CC incidence was the highest in the 55-59 age group, globally. The risk factors, which included unsafe sex and smoke, significantly varied by region. The global ASIR exhibited a downward trend from 2021 to 2035.ConclusionFrom 1990 to 2021, although the overall trend in incidence, mortality, and DALYs of CC exhibited a global and regional downward trend, there were significant disparities among areas with different socioeconomic development. More efficient targeted prevention and management strategies, easy access to health care in less developed regions, and risk factor modifications should be promoted, in order to reduce the global burden of CC.